Sibling Aggression Among Clinic-Referred Children and Adolescents. Issue 6 (2nd November 2018) - Tompsett, Carolyn J.; Mahoney, Annette; Lackey, Jennifer
Abstract : Aggression against siblings has been associated with a number of negative outcomes within community samples of children and adolescents, but little is known about this phenomenon within clinical samples. The current study empirically identified subtypes of sibling aggression, assessed prevalence within a clinic-referred sample of children and adolescents, and described risk factors associated with sibling aggression. Surveys were administered as part of the intake procedures at a community mental health center serving children and adolescents. The current study analyzed reports of sibling-directed aggression and mother-to-child aggression, as well as symptom counts, from a sample of 346 matched pairs of mothers and children or adolescents. Ages of child/adolescent participants ranged from 7 to 18 (M = 12.92, SD = 2.82) and were 55.8% male. The sample was primarily Caucasian (90.2%), were lower income, and resided in a semirural midwestern county. Sibling-directed aggression was reported by 93.1% of mothers and 82.4% of children. Principal components analyses identified two subtypes of sibling aggression, mild and severe. Mother and child/adolescent reports of sibling aggression demonstrated only moderate agreement. Mother-to-child verbal aggression and corporal punishment were more predictive of sibling aggression than more severe maternal aggression, and externalizing symptoms were also associated with sibling aggression. Sibling-directed aggression is very common among clinic-referred children and adolescents and may be an important target for treatment. Using multiple reports of sibling aggression could increase the chances of detection, as would awareness of other risk factors associated with sibling aggression.